PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVMENT DIVISION (STAD) TERHADAP KEAKTIFAN DAN HASIL BELAJAR FISIKA PADA MATERI GELOMBANG SISWA KELAS XII IPA SMA NEGERI 2 KABUPATEN SORONG - KADANG, ST AMINAH; NAINGGOLAN, JONNER (Jurnal Ilmu Pendidikan Indonesia, 2018)
This study aims to determine the effect of cooperative learning model Student Teams Achievement Division (STAD) on activity and learning outcomes of students studying physics of matter waves semester of class XII student IPA 1 SMAN 2 Sorong. The design used in this study is a quasi experimental design with non-equivalent control group pretest - pottest design. The population of the entire students of class XII Science SMAN 2 Sorong consisting of XII IPA 1 XII IPA 2, XII and XII IPA 3 IPA 4 totaled 143 students. The samples used were students of class XII IPA 3 totaling 36 students and class XII IPA 1 as many as 36 students sampling technique is purposive sampling. Data obtained from studies conducted data normality test, homogeneity and liniearitas. Data is then performed with less hypothesis test t test and simple regression. The results obtained by the learning outcomes of students who applied learning with the classical model obtained difference before and after pembelajaran.Hasil learning students who applied learning model STAD obtained difference before and after learning. The results of student learning different control and experimental groups. Control group students' learning activeness of the different experimental groups. Application of Learning Model STAD has a significant effect on students' learning activeness by 41.1%. and also affects the learning outcomes of students with pengruh value which is equal to 37.2%